Biancaneve e sette anni - Fagioli, Massimo (Il sogno della farfalla, 2023)
In this issue, the article written by the psychiatrist Massimo Fagioli which appeared for the first time in the journal “Psychotherapy and Human Sciences” in the issue of October-December 1979, as a comment to a paper by A. Poggiali, is republished. This article written by Poggiali, which had appeared in the previous issue of the journal, seven years after the publication of Death instinct and knowledge, proposed an harsh critic to Fagioli’s theory, affirming how this was in line with the freudian tradition. In Fagioli’s response letter, the author reaffirms the absolute originality of his personal discovery compared to the psychoanalytic world. Drawing by the critics received, the psychiatrist furtherly exposes a method of thinking which reveals to be absolutely unprecedented compared to the past.